Perancangan Interior Kafe Pecinta Anjing di Surabaya - Tjen, Febrila Chendra (Intra, 2013)
Dogs are social animals, which because of the proximity of human behavior patterns by making a dog can be trained, to play, live with humans, and invited socialization with humans. Thats why a lot of people that make a dog is just like a friend as well as your own. The Interior of Dog Lovers cafÃ© is a place to be able to meet the needs of dog lovers and can be a facility to realize the wishes of dog lovers who want to introduce the dog to the general public. Besides the lack of similar facilities in Surabaya. Facilities provided include a reception area, indoor cafe, outdoor cafe, galleries, libraries, clothing stores, souvenir shops, and a photoroom. The concept of the design is to create an attractive atmosphere that can attract visitors.